The Coffee Market in Brazil: challenges and policy guidelines - Caldarelli, Carlos Eduardo; Gilio, Leandro; Zilberman, David (Revista de Economia, 2019)
This paper aims to analyze the coffee market in Brazil post-1990 (deregulation) highlighting the mains challenges in this agrichain. We’ve evaluated the Brazilian competitiveness position of this crop towards the most important competitors in the global market and draft some policy guidelines to enhance the Brazilian competitiveness, such as technology, certification, geographical indication, traceability and the strengthen of the quality and marketing of the Brazilian coffee.